Fluorescence Anion Chemosensor Array Based on Pyrenylboronic Acid - Cao, Zhenbo; Cao, Yang; Kubota, Riku; Sasaki, Yui; Asano, Koichiro; Lyu, Xiaojun; Zhang, Zhoujie; Zhou, Qi; Zhao, Xiaolei; Xu, Xu; Wu, Si; Minami, Tsuyoshi; et al. (Frontiers in Chemistry, 2020)
A novel fluorescence chemosensor array composed of pyrenylboronic acid-based probes for multi- anion detection has been developed. The pyrenylboronic acid derivatives showed fluorescence quenching or enhancement due to photoinduced electron transfer originated from anion binding. The recognition ability was assessed by fitting of the fluorescence titration isotherms and measuring electrospray ionization mass spectrometry. Because the array is constructed with the cross-reactive sensor elements, the combination of differential binding affinities for anions (i.e. fluoride, acetate, oxalate, malonate, citrate, dihydrogen phosphate, and pyrophosphate) and pattern recognitions such as linear discriminant analysis offered a successful simultaneous anion detection with a classification rate of 100%. Furthermore, the chemosensor array allowed quantitative prediction of oxalate, malonate, and citrate in mixtures by using a support vector machine. Importantly, the array system employs low-cost and commercially available reagents as probes. Thus, this study could lead to the development of user-friendly and high-throughput methods to detect a variety of analytes in complicated systems.